EFEKTIVITAS PENGGUNAAN METODE ROLE PLAYING DALAM MENINGKATKAN KEPERCAYAAN DIRI SISWA KELAS IV DI SD NEGRI 182/1 HUTANLINDUNG - Fitri, Elmina; Yatim, Muhammad; Liantori, Beni; Nabila, Kholisatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the application of the role-playing method and determine how it improves the self-confidence of fourth-grade students at SD Negeri 182/1 Hutan Lindung. The underlying problem is low student self-confidence, demonstrated by a lack of courage to speak, low participation in discussions, and fear when answering questions.This study used a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, implemented in two cycles. Each cycle consisted of planning, action, observation, and reflection. Twenty-five students participated in the study. Data were collected through observation, questionnaires, interviews, and documentation, and analyzed using percentage and N-Gain techniques.The results showed an increase in student self-confidence, from 50% in the pre-cycle to 65% in the first cycle and 85% in the second cycle. The N-Gain value of 0.70 is considered high. This increase was influenced by active student involvement, direct learning experiences, and social interactions that occurred during the learning process. Thus, the role-playing method has proven effective in improving student self-confidence.